Water filter: a rapid water environmental DNA collector in the field - Wu, Ping; Feng, Jie; Ju, Mingxia; Wu, Shenhao; Han, Weichun; Wang, Miao; Liao, Junquan; Zhao, Lifeng; Gao, Yifan; Zheng, Jiao; Luo, Mingjie; Gong, Huixian; et al. (Frontiers in Environmental Science, 2024)
Biological monitoring using environmental DNA (eDNA) technology has expanded from micro-to macro-organisms. In aquatic eDNA studies, large volumes of water need to be filtered rapidly in the field, which requires development of effective eDNA collection devices. Here, we introduce a novel portable eDNA collection system containing a GM dual-channel water filter and a DNA extraction kit adapted to large filter membranes (ø 100 mm). The water filter is powered by a high-capacity lithium battery (9000 mA), which operates two peristaltic pumps and maintains a continuous filtration rate of up to 1 L/min for 5 h in outdoor settings. For sample collection, the optimum conditions are still water and turbidity below 8 nephelometric turbidity units. This allows for the filtration of 10 L of water within 10 min using a 0.22-μm filter. Metagenomic and 12S metabarcoding sequencing showed that the DNA extraction quality and species annotation accuracy of our custom DNA extraction kit, which was tailored for this system, rivaled the performance of established kits. The GM water filter's enrichment mode gave consistent results with vacuum filtration, which greatly reduced the filtration time for large water samples while accurately reproducing species annotations. This innovation streamlines the eDNA collection and annotation process and offers substantial benefits for biodiversity monitoring and conservation efforts.